The Begawan Ciptaning scene in the Gagrag Ngayogyakarta puppet show: Representation to approach the self to the essence of the God - Djoko Sulaksono; Tya Resta Fitriana; Prima Veronika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
Puppet stories or shows are literary works that contain didactic moral problems and aesthetic elements. Puppet shows also contain extensive guidelines (piwulang), such as religious values, philosophy, ethics, and character education for human life. Furthermore, the puppet has noble values ​​as role models and illustrations of daily human life (pathet) and crucial to build character and national identity. This study aims to describe and elaborate on the philosophical meaning of the Purwa Puppet of Gagrag Ngayogyakarta style performance, especially the scene of Arjuna’s asceticism or Begawan Ciptaning. This research is a qualitative descriptive study. Data analysis techniques using content analysis. The results of this study indicate the role model of Arjunawiwaha’s story, especially the scene of Arjuna’s asceticism. This scene contains moral values, such as Arjuna’s firmness and persistence in trying to get closer to the essence of the world’s rulers. Another value is devotion to parents and the state, and leadership. The values found in the puppet stories are also relevant to nowadays life and are linked to Islamic thoughts.